Strategies for media literacy: Audiovisual skills and the citizenship in Andalusia - Ignacio Aguaded-Gómez; M. Amor Pérez-Rodríguez (Springer, 2012)
Media consumption is an undeniable fact in present-day society. The hours that members of all social segments spend in front of a screen take up a large part of their leisure time worldwide. Audiovisual communication becomes especially important within the context of today's digital society (society-network), where information and communication technologies pervade all corners of everyday life. However, people do not own enough audiovisual media skills to cope with this mass media omnipresence. Neither the education system nor civic associations, or the media themselves, have promoted audiovisual skills to make people critically competent when viewing media. This study aims to provide an updated conceptualization of the "audiovisual skill" in this digital environment and transpose it onto a specific interventional environment, seeking to detect needs and shortcomings, plan global strategies to be adopted by governments and devise training programmes for the various sectors involved.